Neurodegeneration and Vascular Burden on Cognition After Midlife: A Plasma and Neuroimaging Biomarker Study - Huang, Kuo-Lun; Hsiao, Ing-Tsung; Chang, Ting-Yu; Yang, Shieh-Yueh; Chang, Yeu-Jhy; Wu, Hsiu-Chuan; Liu, Chi-Hung; Wu, Yi-Ming; Lin, Kun-Ju; Ho, Meng-Yang; Lee, Tsong-Hai (Frontiers in Human Neuroscience, 2021)
Background and objectives: Neurodegeneration and vascular burden are the two most common causes of post-stroke cognitive impairment. However, the interrelationship between the plasma beta-amyloid (Aβ) and tau protein, cortical atrophy and brain amyloid accumulation on PET imaging in stroke patients is undetermined. We aimed to explore 1) the relationships of cortical thickness and amyloid burden on PET with plasma Aβ40, Aβ42, tau protein and their composite scores in stroke patients, and 2) the associations of post-stroke cognitive presentations with these plasma and neuroimaging biomarkers. Methods: The prospective project recruited first-ever ischemic stroke patients around 3 months after stroke onset. The plasma Aβ40, Aβ42, and total tau protein were measured with the immunomagnetic reduction method. Cortical thickness was evaluated on MRI, and cortical amyloid plaque deposition were evaluated by 18F-florbetapir PET. Cognition was evaluated with Mini-Mental State Examination (MMSE), Geriatric Depression Scale (GDS), Dementia Rating Scale-2 (DRS-2). Results: The study recruited 24 stroke patients and 13 normal controls. The plasma tau and tau*Aβ42 levels were correlated with mean cortical thickness after age adjustment. The Aβ42/Aβ40 ratio was correlated with global cortical 18F-florbetapir uptake value. The DRS-2 and GDS scores were associated with mean cortical thickness and plasma biomarkers, including Aβ42/Aβ40, tau, tau*Aβ42, tau/Aβ42, and tau/Aβ40 levels, in stroke patients. Conclusion: Plasma Aβ, tau, and their composite scores were associated with cognitive performance 3 months after stroke, and these plasma biomarkers were correlated with corresponding imaging biomarkers of neurodegeneration. Further longitudinal studies with larger sample size are warranted to replicate the study results.